P509 Vedolizumab levels in breast milk: Results from a prospective, postmarketing, milk-only lactation study in nursing mothers with inflammatory bowel disease. (15th January 2020) - Sun, W; Fennimore, B; Beaulieu, D B; Arsenescu, R; Stein, A; Chen, J; Lin, T; McKnight, S; Rosario, M; Lirio, R A
Abstract: Background: The safety of inflammatory bowel disease (IBD) medications during lactation is of significant interest and relevance to female patients of childbearing potential. Available data regarding the safety and transfer of biologic agents via breast milk are limited to case reports. Vedolizumab has a well-established, positive benefit-risk profile in adult IBD patients. Literature data show that vedolizumab is detectable in human milk. Methods: A prospective, postmarketing, phase 4, open-label, milk-only lactation study was conducted to assess vedolizumab concentrations in breast milk from lactating women with IBD who were on an established vedolizumab maintenance regimen (300 mg intravenous [IV] every 8 weeks [Q8W] or an alternative dose frequency). Maternal milk samples were serially collected throughout the dosing interval on Days 1 (predose and 1 h after the end of vedolizumab infusion), 4, 8, 15, 29, and 57 to allow the estimation of drug excreted in milk relative to the maternal dosage. Maternal safety data were also collected. Results: A total of 11 patients were enrolled in the study. Vedolizumab was detectable in the majority of milk samples collected on Days 1 and 57, and in all samples collected at other time points. Following receipt of vedolizumab 300 mg IV on Day 1, the vedolizumab milk concentration increased with a median time to peak concentration (Cmax ) of 3–4 days, and subsequently decreased exponentially. For the 9 patients on the Q8W regimen, median Cmax was 0.213 µg/ml (range, 0.098–0.561 µg/ml); the geometric mean daily infant dosage, calculated using average concentration over 8-week dosing interval (0.13 µg/ml), was 0.02 mg/kg/day with a corresponding geometric mean percentage of maternal dosage consumed in breast milk by infants of 21%. The maternal safety profile was acceptable and similar to that observed in previous adult studies. Leveraging the mean trough serum concentration of 11.2 µg/ml from historical studies of vedolizumab, the ratio of mean milk concentration (trough, 0.05 µg/ml; peak, 0.25 µg/ml) to serum concentration was approximately 0.4%-2.2%, which is consistent with published data for vedolizumab and comparable with several other monoclonal antibody therapeutics for IBD. Published vedolizumab studies also showed no increase in general or gastrointestinal tract infections in the infants exposed to vedolizumab in breast milk, and exposed infants reached their acceptable development milestones through up to 10 months of follow-up. Conclusion: Vedolizumab was found to be present in human breastmilk at a low level. The impact of vedolizumab IV administration during breastfeeding is expected to be minimal.